Magnesium sulphate fertilization for yield enhancement in direct seeded rice - Daly George (Department of Agronomy, College of Agriculture, 2018)
The study entitled “Magnesium sulphate fertilization for yield enhancement in direct seeded rice” was conducted at College of Agriculture, Vellayani, Thiruvananthapuram, Kerala from 2016 - 2018 July, to determine the optimum dose, time and method of application of magnesium sulphate (MgSO4) for growth and yield enhancement in rice. The study was conducted in farmer’s field at Kalliyoor Panchayat, Thiruvananthapuram district during May to September 2017. The experiment was laid out in randomized block design (RBD) with fourteen treatments and three replications. The variety used was Sreyas (MO 22) released from Rice Research Station, Moncompu, Kerala. The treatments were; T1 -MgSO4 @ 20 kg ha-1 at 20 days after sowing (DAS), T2 -MgSO4 @ 30 kg ha-1 at 20 DAS, T3 -MgSO4 @ 40 kg ha-1 at 20 DAS, T4 -MgSO4 @ 20 kg ha-1 in two equal splits at 20 and 40 DAS, T5 - MgSO4 @ 30 kg ha-1 in two equal splits at 20 and 40 DAS, T6 - MgSO4 @ 40 kg ha-1 in two equal splits at 20 and 40 DAS, T7 -MgSO4 @ 10 kg ha-1 at 20 DAS and 1 % MgSO4 at 40 DAS as foliar spray, T8- MgSO4 @ 15 kg ha-1 at 20 DAS and 1 % MgSO4 at 40 DAS as foliar spray, T9- MgSO4 @ 20 kg ha-1 at 20 DAS and 1 % MgSO4 at 40 DAS as foliar spray, T10 -MgSO4 @ 10 kg ha-1 at 20 DAS and 2 % MgSO4 at 40 DAS as foliar spray , T11-MgSO4 @ 15 kg ha-1 at 20 DAS and 2 % MgSO4 at 40 DAS as foliar spray, T12- MgSO4 @ 20 kg ha-1 at 20 DAS and 2 % MgSO4 at 40 DAS as foliar spray, T13 -MgSO4 @ 80 kg ha-1 as basal (ad hoc recommendations of Kerala Agricultural University (KAU)) and T14- Control (Package of Practices Recommendations crops 2016 Kerala Agricultural University (KAU PoP) without Mg). All the treatments were given a uniform dose of FYM @ 5 t ha-1, lime @ 600 kg ha-1 in two splits and NPK @ 90: 45: 45 kg ha-1 (KAU, 2016). The results revealed that growth attributes like plant height and tillers m-2 at maximum tillering, panicle initiation (PI) and harvest stages and the leaf area index (LAI) at panicle initiation stage were significantly influenced by MgSO4 fertilization. At maximum tillering stage, the height of the plant was the highest in T2, at panicle initiation stage it was the highest in T10. At both maximum tillering and panicle initiation stages, tillers m-2 were the highest in T9, while at harvest it was the highest in T4. The LAI at panicle initiation stage was found the highest in T6. Early flowering was observed in T6, similarly the root shoot ratio was also found the highest in T6. Late flowering and the lowest root shoot ratio were observed in T14 (control -KAU PoP without Mg). Chlorophyll content at panicle initiation and boot leaf stages were significantly higher in Mg applied treatments compared to control. The yield and yield attributing characters were also significantly influenced by the dose, time and method of application of MgSO4. The panicle weight (2.89 g), number of filled grains panicle-1 (133.2), grain yield (9.6 t ha-1) and harvest index (0.463) were the highest in T6. The availability of primary and secondary nutrients in soil and its uptake at maximum tillering, panicle initiation and harvest stages were also influenced by the treatments. The availability of Mg in soil at harvest was slightly increased due to MgSO4 fertilization. The uptake of K and Mg showed an antagonistic interaction and Mg uptake at all stages was lower in control (KAU PoP without Mg). The quality attributes like protein and Mg content in grain were also higher in treatments receiving Mg. Economic analysis showed the significance of Mg application and also its split application over control (KAU PoP without Mg) and T13 (MgSO4 @ 80 kg ha- 1 as basal (ad hoc recommendations)). The B:C ratio in T6 was 3.01 whereas in control it was 2.46 and in T13 it was 2.42. From the study, it can be concluded that MgSO4 fertilization significantly enhanced the yield and quality of rice irrespective of method of application. However considering the net income and B:C ratio, soil application of MgSO4 @ 20 or 40 kg ha-1 in two equal splits at 20 and 40 DAS (depending upon Mg availability in soil) can be given as recommendation for farmers for getting higher grain yield.